Bacterial antimicrobial resistance and dermatological ramifications. (1st July 2022) - Muhaj, Fiorinda F.; George, Saira J.; Tyring, Stephen K.
Summary: The spread of COVID‐19 serves as a reminder of the might of microbes in the era of modern medicine. For years, another threat has preoccupied infectious disease experts and public health officials alike: rising antimicrobial resistance (AMR). Resistance is exceeding stewardship efforts as well as the rates of new drug development and approval in the market. A dry antimicrobial pipeline is threatening regression to a preantibiotic era. While the consequences of resistance may seem far removed from daily clinical practice, awareness of AMR is essential to dermatological care given that dermatologists prescribe more antibiotics per physician than other providers. Antibiotics in dermatology are often used for prolonged courses, with significant potential for microbiome alteration and antibiotic‐related adverse effects. Through this review we hope to contribute to efforts of bringing the crisis of AMR to the forefront of daily dermatological practice.